We are all smokers! - Shalihin, Mohd Shaiful Ehsan (Malaysian Medical Gazette, 2018)
Do you realise, that all of us are “Smokers”? What should we do? Do you feel that the number of smokers in the world, in general, and specifically in Malaysia, is shrinking? Are you confident that the world community is becoming more aware of the dangers of smoking? Are you sure the struggle to prevent smoking is effective? Do you feel that staying at home is actually safe? And that you have nothing to worry about? You cannot be further from the truth!